The breeding strategy of female jumbo squid Dosidicus gigas: energy acquisition and allocation - Chen, Xinjun (Sci Rep, 2020)
Reproductive investment generally involves a trade-off between somatic growth and energy allocation for reproduction. Previous studies have inferred that jumbo squid Dosidicus gigas support growth during maturation through continuous feeding (an “income” source). However, our recent work suggests possible remobilization of soma during maturation (a “capital” source). We used fatty acids as biochemical indicators to investigate energy acquisition and allocation to reproduction for female D. gigas. We compared the fatty acid profiles of the ovary to those of the mantle muscle (slow turnover rate tissue, representing an energy reserve) and the digestive gland (fast turnover rate organ, reflecting recent consumption). For each tissue, the overall fatty acids among maturity stages overlapped and were similar. The changes with maturation in fatty acid composition in the ovary consistently resembled those of the digestive gland, with the similarity of fatty acids in the mantle muscle and the ovary increasing during maturation, indicating some energy reserves were utilized. Additionally, squid maintained body condition during maturation regardless of increasing investment in reproduction and a decline in feeding intensity. Cumulatively, D. gigas adopt a mixed income-capital breeding strategy in that energy for reproduction is mainly derived from direct food intake, but there is limited somatic reserve remobilization.